Left Atrial Appendage Occlusion: Expanding Indications and New Developments - Grant W. Reed, MD, MSc; Shady Nakhla, MD; Rhonda Miyasaka, MD; Serge Harb, MD; Mohamed Kanj, MD; Ousamma Wazni, MD; Samir R. Kapadia, MD; Amar Krishnaswamy, MD (Structural Heart)
Percutaneous left atrial appendage occlusion (LAAO) is recommended in several major international society guidelines as a viable alternative to therapeutic anticoagulation for the prevention of ischemic stroke in patients with nonvalvular atrial fibrillation or flutter. Recent innovations in device development have improved the safety and procedural success of LAAO, further fueling enthusiasm for expanding its indications beyond patients with high-bleeding risk from oral anticoagulation use. It is the aim of this review to provide historical context in addition to recent updates and upcoming developments and provide practical suggestions on how best to care for patients who are candidates for LAAO in contemporary practice. Recent data comparing the safety and efficacy of post-LAAO antiplatelet vs. antithrombotic therapy will be highlighted, with specific recommendations regarding which patients are best suited for each strategy. We will also address the safety and practical considerations provided by emerging trials on concomitant LAAO during other structural heart interventions such as transcatheter aortic valve replacement and mitral valve interventions, as well as electrophysiology procedures including catheter ablation for atrial fibrillation and pacemaker implantation. Practical considerations for the use of transesophageal echocardiography or intracardiac echocardiography for procedural guidance will also be discussed. As the evidence supporting LAAO continues to evolve, this review will serve as a primer on the recent and upcoming advances in device technology and management strategies positioned to further push LAAO forward into the future.